2020
DOI: 10.1124/jpet.120.266171
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Region-Specific Differences in the Transcriptomes of Rat Microglia from the Brainstem and Cervical Spinal Cord

Abstract: The neural control system underlying breathing is sexually dimorphic with males being more vulnerable to dysfunction. Microglia also display sex differences, and their role in the architecture of brainstem respiratory rhythm circuitry and modulation of cervical spinal cord respiratory plasticity is becoming better appreciated. To further understand the molecular underpinnings of these sex differences, we performed RNA sequencing of immunomagnetically isolated microglia from brainstem and cervical spinal cord o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 93 publications
0
12
0
1
Order By: Relevance
“…Microglia are the professional immune cells in the CNS and thus are the first responders to brain injury or infection. However, current knowledge shows that microglia are also a highly heterogeneous cell population, with sex- and region-specific differences that exert a plethora of physiological roles in healthy CNS including patrolling of brain parenchyma, clearing apoptotic cells and other debris, regulating neuronal plasticity by participating in synaptic pruning, and responding to signals from peripheral immune system (Wilton et al., 2019; Ewald et al., 2020; Gerrits et al., 2020). Following CNS viral infection, microglial cells become rapidly activated and release proinflammatory molecules and reactive oxygen species, recruit cells of the peripheral immune system, and activate astrocytes (Ransohoff and Perry, 2009; Chatterjee et al., 2013; Wheeler et al., 2018).…”
mentioning
confidence: 99%
“…Microglia are the professional immune cells in the CNS and thus are the first responders to brain injury or infection. However, current knowledge shows that microglia are also a highly heterogeneous cell population, with sex- and region-specific differences that exert a plethora of physiological roles in healthy CNS including patrolling of brain parenchyma, clearing apoptotic cells and other debris, regulating neuronal plasticity by participating in synaptic pruning, and responding to signals from peripheral immune system (Wilton et al., 2019; Ewald et al., 2020; Gerrits et al., 2020). Following CNS viral infection, microglial cells become rapidly activated and release proinflammatory molecules and reactive oxygen species, recruit cells of the peripheral immune system, and activate astrocytes (Ransohoff and Perry, 2009; Chatterjee et al., 2013; Wheeler et al., 2018).…”
mentioning
confidence: 99%
“…These findings are most prominent in the hippocampus and amygdala-brain regions which have also been implicated in ASD [172,173]. Animal studies have also identified sex differences in the microglia transcriptome [174].…”
Section: Male Biasmentioning
confidence: 91%
“…Они происходят из эмбриональных предшественников желточного мешка, которые колонизируют ЦНС на ранних стадиях развития [33]. Современные знания показывают, что микроглия также представляет собой весьма гетерогенную популяцию клеток, которые выполняют множество физиологических функций в ЦНС, включая иммунный контроль нервной ткани, фагоцитоз апоптотических клеток и продуктов нейрональной дегенерации, регулирование нейрональной пластичности, отвечают на сигналы периферической иммунной системы [27].…”
Section: реакция нейроглии на вирусную инвазию и ее вклад в развитие unclassified